Malignancy and IFITM3: Friend or Foe? - Rajapaksa, Ushani S.; Jin, Chen; Dong, Tao (Frontiers in Oncology, 2020)
The prevalence and incidence of cancers has risen over the last decade. Available treatments have improved outcomes, yet mortality and morbidity remain high, creating an urgent demand for personalized and new therapy targets. Interferon induced transmembrane protein (IFITM3) is highly expressed in cancers and is a marker of poor prognosis. In this review, we discuss recent advances in IFITM3 biology, the regulatory pathways, and its function within cancer as part of immunity and maintaining stemness. Overexpression of IFITM3 is likely an indirect effect of ongoing inflammation, immune and cancer epithelial-to-mesenchymal (EMT) related pathways i.e., interferons, TGF-β, WNT/β-catenin, etc. However, IFITM3 also influences tumorigenic phenotypes, such as cell proliferation, migration and invasion. Furthermore, IFITM3 plays a key role in cancer growth and maintenance. Silencing of IFITM3 reduces these phenotypes. Therefore, targeting of IFITM3 will likely have implications for potential cancer therapies.